M9 Lung Health of OPiate Users (LHOp): A pilot study to assess the respiratory health of opiate misusers attending a community substance misuse clinic. (12th November 2015) - Pitt, A; Mitchell, C; Colwell, B; Appelqvist, I; Ashby, F; Lloyd, C; Gilbody, S; Lawson, R
Abstract : Introduction: MDTs promote harm reduction in the care of opiate misusers (OMUs) through the prescription of opiate substitute medication and by encouraging smoking rather than injecting (to reduce the risk of blood-bourne virus transmission and venous thromboembolism). The average life expectancy for a male OMU is 41 years and whilst evidence suggests that the current cohort of older OMUs are dying prematurely from non-drug related deaths, all-cause mortality studies rarely report the prevalence of chronic health problems. A recent case-controlled study reported a higher prevalence of asthma and COPD in OMUs after adjusting for tobacco consumption and other factors. The study objective was to investigate the prevalence and illness burden of respiratory problems (asthma, COPD, symptomatic but undiagnosed lung disease) in patients with a history of current and/or past opiate misuse. Methods: Opportunistic clinic-based participant recruitment. Resting spirometry and researcher administered socio-demographic, inhaled drug use and validated respiratory patient reported outcome questionnaires: 1) prior diagnosis of asthma (ACT; mini-ARQoL) or COPD (CCQ); 2) respiratory health screening if no prior diagnosis (LFQ). Results: There were 36 participants (26 male; 10 female; aged 24–53). Only 8 had a diagnosis (all asthmatics); 35/36 smoked tobacco; 34/36 smoked heroin; 33/36 smoked cocaine; and 31/36 smoked cannabis. All asthmatics had poor control (<13) on the ACT (median score 8) and frequent beta-agonist use (none used inhaled corticosteroids). Of the others, 22/28 scored ≤18 on LFQ suggesting high symptom burden and three of these had obstructive resting spirometry increasing the possibility of COPD. Conclusions: Chronic respiratory health in drug users is an under-researched area with few screening or high quality intervention studies evident. We identified a significant respiratory symptom burden within this OMU cohort. Most smoked tobacco, heroin, cocaine and cannabis. Asthmatics reported poor control and were potentially at risk of severe exacerbations, hospital admission and early progression to COPD. Four further LHOp studies are planned: a pharmacy based intervention to improve asthma control/uptake of preventive interventions (smoking cessation; vaccinations); a case control study of GP asthma medication prescribing; prospective prognostic respiratory health cohort studies; and a qualitative study of asthmatic OMUs' perspectives on respiratory health and inhaler use.